Involuntary unemployment and the business cycle - Lawrence Christiano; Mathias Trabandt; Karl Walentin (European Central Bank (ECB), 2010)
We propose a monetary model in which the unemployed satisfy the official US definition of unemployment: they are people without jobs who are (i) currently making concrete efforts to find work and (ii) willing and able to work. In addition, our model has the property that people searching for jobs are better off if they find a job than if they do not (i.e., unemployment is `involuntary'). We integrate our model of involuntary unemployment into the simple New Keynesian framework with no capital and use the resulting model to discuss the concept of the `non-accelerating inflation rate of unemployment'. We then integrate the model into a medium sized DSGE model with capital and show that the resulting model does as well as existing models at accounting for the response of standard macroeconomic variables to monetary policy shocks and two technology shocks. In addition, the model does well at accounting for the response of the labor force and unemployment rate to the three shocks.
Keywords: E2; E3; E5; J2; J6; 330; Bayesian estimation; business cycles; DSGE; monetary policy; Unemployment; Dynamisches Gleichgewicht; Theorie der unfreiwilligen Arbeitslosigkeit; Konjunktur; Phillips-Kurve; Geldpolitik; Bayes-Statistik